Ultrahigh energy storage density lead-free multilayers by controlled electrical homogeneity. Issue 2 (15th January 2019) - Wang, Ge; Li, Jinglei; Zhang, Xun; Fan, Zhongming; Yang, Fan; Feteira, Antonio; Zhou, Di; Sinclair, Derek C.; Ma, Tao; Tan, Xiaoli; Wang, Dawei; Reaney, Ian M.
Abstract : Introducing controlled electrical homogeneity can be an effective way to obtain ultrahigh energy storage density in lead-free multilayers. Abstract : Ultrahigh discharge energy density ( W dis = 10.5 J cm −3 ) and efficiency ( η = 87%) have been obtained in doped BiFeO3 –BaTiO3 ceramic multilayers by achieving an electrically rather than chemically homogeneous microstructure. Back scattered scanning and transmission electron microscopy combined with energy dispersive X-ray spectroscopy mapping of (0.7 − x )BiFeO3 –0.3BaTiO3 – x Nd(Zn0.5 Zr0.5 )O3 (0.05 ≤ x ≤ 0.10) ceramics revealed a core–shell grain structure which switched from a bright to dark contrast as x increased. Compositions with x = 0.08 were at the point of cross over between these two manifestations of core–shell contrast. Dielectric measurements together with the absence of macrodomains in diffraction contrast TEM images suggested that compositions with x = 0.08 exhibited relaxor behaviour within both the core and shell regions. Impedance spectroscopy demonstrated that, despite being chemical dissimilar, the grains were electrically homogeneous and insulating with little evidence of conductive cores. Multilayers of x = 0.08 had enhanced breakdown strength, E BDS > 700 kV cm −1 and a slim hysteresis loop which resulted in large W dis and high η which were temperature stable to <15% from 25 to 150 °C.